Characterising early human lympho-myeloid haematopoietic progenitors and their relationship with acute myeloid leukaemia stem cells - Aboukhalil, Z (2018)
Haematopoiesis is a quintessential cellular hierarchy, with the haematopoietic stem cell having the ability to produce all blood cells. Downstream of the stem cell are multiple progenitor populations with increasing lineage-restriction. However, our knowledge of the progenitors that produce the lymphoid and myeloid lineages remains incomplete. Furthermore, in acute myeloid leukaemia there is a differentiation arrest at the lympho-myeloid progenitor stage, with the development of a progenitor-like leukaemia stem cells. A thorough comparison of the progenitor-like leukaemia stem cell with normal stem and progenitor cells is yet to be completed. Presented here is a comprehensive study of the lympho-myeloid progenitors in both normal and leukaemic haematopoiesis. Firstly, the normal lympho-myeloid progenitors were fully characterised, both functionally and transcriptionally. Extensive single-cell analysis allowed the heterogeneity and continuum underlying lympho-myeloid differentiation to be uncovered. Although the majority of single-cells generated only one mature lineage, rare multi-lineage single-cells were detected. The lympho-myeloid progenitors were then studied in acute myeloid leukaemia. It was demonstrated that there is often an expansion of the lympho-myeloid progenitors, which develop leukaemia-propagating ability. Transcriptionally, it was seen that the leukaemia stem cells displayed dysregulated expression profiles, whilst retaining some resemblance to the normal progenitors. A set of genes upregulated in the leukaemia stem cell was identified, and it was proposed that six of these genes may play a role in leukaemogenesis. Studying both normal and leukaemic haematopoiesis is essential in advancing the treatment of acute myeloid leukaemia. Firstly, a more thorough understanding of the process of normal lympho-myeloid differentiation may aid the development of differentiation therapies. Secondly, by identifying functionally relevant markers of the leukaemia stem cell, treatments targeting the apex of the leukaemic hierarchy may be developed. And through the eradication of the leukaemia stem cell, we may truly eliminate the leukaemic disease.